Striking the Balance: GLP-1/Glucagon Co-Agonism as a Treatment Strategy for Obesity - Hope, David C. D.; Vincent, Matthew L.; Tan, Tricia M. M. (Frontiers in Endocrinology, 2021)
Obesity and Type 2 diabetes represent global health challenges, and there is an unmet need for long-lasting and effective pharmacotherapies. Although long-acting glucagon-like peptide 1 (GLP-1) analogues are now in routine use for diabetes and are now being utilised for obesity per se, the need for ever better treatments has driven the development of co-agonists, with the theoretical advantages of improved efficacy by targeting multiple pathways and reduced adverse effects. In this review, we highlight the past and present progress in our understanding and development of treatments based on GLP-1/glucagon co-agonism. We also reflect on the divergent effects of varying the GLP-1:glucagon activity and ratio in the context of pre-clinical and human clinical trial findings. In particular, the multiple metabolic actions of glucagon highlight the importance of understanding the contributions of individual hormone action to inform the safe, effective and tailored use of GLP-1/glucagon co-agonists to target weight loss and metabolic disease in the future.